2014
DOI: 10.1016/j.neuroimage.2013.08.045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of color priming on infant brain and behavior

Abstract: Behavioral studies have identified select experiences that can prime infants to attend to color information as the basis for individuating objects prior to the time they do so spontaneously. For example, viewing pretest events in which the color of an object predicts the function in which it will engage leads 9-month-olds (who typically do not attend to color differences) to demonstrate increased sensitivity to color information in a subsequent individuation task (Wilcox & Chapa, 2004). In contrast, viewing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 39 publications
3
42
0
1
Order By: Relevance
“…Whereas there have been previous investigations of object processing using fNIRS, these studies have not focused on uncovering shape-selective regions per se and have instead focused on how object identity modulates activity in the inferior temporal cortex (Wilcox et al, 2008(Wilcox et al, , 2014Wilcox and Biondi, 2015) or responds to faces, as a visual category, compared with baseline nonface stimuli (Otsuka et al, 2007;Honda et al, 2010). However, although the current study augments our stimuli with faces to maintain infant attention, facial information is identical across conditions (the eyes and mouth are identical for all stimuli), and whereas we did vary eye gaze across shapes (and thus this varies between variable and repeated blocks), this does not change across conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas there have been previous investigations of object processing using fNIRS, these studies have not focused on uncovering shape-selective regions per se and have instead focused on how object identity modulates activity in the inferior temporal cortex (Wilcox et al, 2008(Wilcox et al, , 2014Wilcox and Biondi, 2015) or responds to faces, as a visual category, compared with baseline nonface stimuli (Otsuka et al, 2007;Honda et al, 2010). However, although the current study augments our stimuli with faces to maintain infant attention, facial information is identical across conditions (the eyes and mouth are identical for all stimuli), and whereas we did vary eye gaze across shapes (and thus this varies between variable and repeated blocks), this does not change across conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although current findings do not provide evidence about face perception, they do bear on the question of how object perception develops early in life and build from the work of Wilcox and colleagues. Broadly, Wilcox and colleagues have found that the infant inferior temporal cortex selectively tracks object-individuation events (i.e., a greater response when a new object is introduced through a change in shape compared with trials where the types of visual movements where shape and other individuation cues are held constant; Wilcox et al, 2008Wilcox et al, , 2014. In addition to temporal lobe recordings, Wilcox et al (2008) included fNIRS recordings from low-level visual areas and did not target the LOC specifically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Despite the rapid growth in the number of infant fNIRS publications in recent years, this number is relatively low when compared to that of adult studies. 18 Infants are certainly more difficult to study, as they cannot be instructed to remain still, unlike an adult subject.…”
Section: Introductionmentioning
confidence: 99%